"Design and development of raisin washing machine". (2021) - Pawar, Raviraj S.; Chavan, S.P.; Limaye, S.H.
Abstract: A prototype of mechanical fruit washer was developed and evaluated for its performance. It has been observed that washing of fruits are mostly done manually. This method is inefficient and time consuming. Hence, there is a need to mechanize this process for ease of operation. An attempt has been made to develop a fruit washer which is conceptualized to wash a range of fruits based on roundness or spherical shape. The machine is designed with essential components being the inner drum, outer drum, vibratory tray, rectangular plate, chain drive, bearings, main frame and discharge outlet. The inner drum rotates at three different speeds (800, 850 and 950 rpm). The raisins were used for evaluation of washers. The higher washing efficiency (98.28%) was observed for speed at 800 rpm. Highest capacity (1940 kg/hr) was found with 97% washing efficiency at 950 rpm. The machine has been developed with the locally available materials powered by 2hp electric motor. The machine was designed for ergonomic value, safety and ease of operation and maintenance by incorporating guards around the moving parts and components.